Isolation and identification of microorganisms associated with automated teller machines on Federal Polytechnic Ede campus. - O G Dawodu (Public Library of Science (PLoS), 2021)
Automated Teller Machines (ATM) are visited everyday by millions of people. This machine is accessible to the general public irrespective of class, age or race. The contact point of all ATM machines is the hand which on their own are 'vaults' of microorganisms. An elaborate survey was taken for complete assessment of possible microbial contamination in the Federal Polytechnic Ede campus. Selected ATM machines on campus were used as case study to characterize, identify and determine the degree of bacterial contamination of microorganisms and their potential as reservoir of microbes. Swabs were collected from each ATM screen, buttons, floor, user's hand, and exposure of plates. After collection of the samples, they were plated in nutrient agar. The results showed the presence of increased bacterial count subsequently, most pathogens on characterization revealed the genus of the particular organisms E. coli, Pseudomonas, Staphylococcus aureus, Klebsiella, Micrococcus, Salmonella and Serratia. The study showed the potential hazard inherent in ATM machine usage and draws attention to our level of hand hygiene compliance.